Cognitive psychopathology: The role of emotion - Power, Michael J. (2011)
This paper examines the role of emotion in the understanding of psychopathology. The influential Cognitive Therapy model of Beck is briefly reviewed and a number of limitations are considered. Two particular weaknesses are highlighted in the understanding of cognitive psychopathology; namely, the importance of multi-level processing systems and the importance of emotion. The Power and Dalgleish (1997, 2008) SPAARS model is presented to show the advantages that arise from the inclusion of multilevel processes combined with a theoretical account of emotion. In order to illustrate the application of the SPAARS model to cognitive psychopathology, findings from a recent emotion profile analysis of clinical depression and anxiety are summarised. The analyses also illustrate the importance of shamerelated emotions in depression in contrast to the guiltrelated emotions that are highlighted in classification systems such as DSM-IV. ------ RESUMO ------ Neste artigo fazemos uma reflexão sobre o papel da emoção na compreensão da psicopatologia. Fazemos uma breve revisão e apontamos uma série de limitações. do influente modelo da Psicoterapia Cognitiva preconizado por Beck. Dois pontos particularmente fracos são destacados na compreensão da psicopatologia cognitiva; nomeadamente, a importância dos sistemas de processamento multi-nível e a importância das emoções. Apresentamos o modelo SPAARS de Power e Dalgleish (1997, 2008), para mostrar as vantagens que resultam da inclusão de processos de multi-nível combinados com uma teoria relacionada com as emoções. Com o objectivo de ilustrar a aplicação do modelo SPAARS à psicopatologia cognitiva. Referimos, de forma sucinta, o que foi observado numa recente analise sobre o perfil da depressão e ansiedade clínicas. Estas analises ilustram também a importância das emoções relacionadas com a vergonha na depressão, em contraste com as emoções relacionadas com a culpa que são destacadas em sistemas de classificação como o DSM-IV.